POLYMORPHISMS OF EXTRACELLULAR CONNECTIVE TISSUE REMODELING PROTEINASES AND MMP2, MMP3, MMP9 GENES, AND NEOANGIGENESIS VEGF GENE IN RETINAL MICROANGIOPATHY IN THE PATIENTS WITH TYPE 2 DIABETES MELLITUS - A. V. Shevchenko; V. F. Prokofiev; V. I. Konenkov; V. V. Klimontov; N. V. Tyan; D. V. Chernykh; A. N. Trunov; V. V. Chernykh (Медицинская иммунология)
The aim of our study was to perform an association analysis between MMP2, MMP3, MMP9, VEGF gene polymorphisms and development of non-proliferative diabetic retinopathy (DR) in the type 2 diabetic patients (DM).201 DM patients: 90 cases of DR and 111 subjects without DR features were included into the study. Polymorphic variants of MMP2 (rs2438650), MMP3 (rs3025058), MMP9 (rs3918242), and VEGF (rs699947 and rs3025039) genes were assayed. The genetic typing was carried out by restriction fragment length polymorphism and TaqMan methods.The analysis of complex genotypes at the five polymorphic positions has revealed some significant findings in positive and negatively incorporated complexes. Increased frequencies of MMP2-1306 CC genotype in the group of patients with “early” development of complication, and more frequent combination of high-level HbA1c with MMP2-1306CC and MMP9-1562CT genotypes were shown in DR patients. Computerassisted modelling with visual reconstruction of network interactions between the genotypes involved into the destruction events and angiogenesis, as well as altered HbA1с levels (an integral parameter of glycemia), has revealed some differences in structural and functional organization of gene-gene and gene- protein interactions between the groups of patients with DR versus those without this disorder. Сonclusion. A design of interactome biological networks based on transcription regulation and metabolic pathways, as well as their topological analysis allows to build and study interactions of genes and proteins, with reference to pathogenetic studies of DM2 complications aiming for development of approaches to personalized prevention and therapy in future times.